2018
DOI: 10.1007/s15010-018-1164-y
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Candida auris infections in Kuwait hospitals: epidemiology, antifungal treatment and outcome

Abstract: Occurrence of successive cases of invasive C. auris infections with resulting mortality in nine patients suggests persistence of this multidrug-resistant yeast in major hospitals in Kuwait. Early detection by continuous surveillance and enforcement of infection control measures are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 41 publications
2
39
0
2
Order By: Relevance
“…Present results concur with a study in Kuwait reported multidrug resistance and high mortality rate among cases of C. auris infections (29). Also, two studies in Oman reported of C.…”
Section: Resultssupporting
confidence: 92%
“…Present results concur with a study in Kuwait reported multidrug resistance and high mortality rate among cases of C. auris infections (29). Also, two studies in Oman reported of C.…”
Section: Resultssupporting
confidence: 92%
“…The number of patients affected is probably underestimated due to difficulties with identification of C. auris because of the lack of proper laboratory support. We report the first case of C. auris in Iran which adds up now to a total of five countries around the Persian Gulf, that is Kuwait, Oman, United Arab Emirates and Saudi Arabia . Choi et al reviewed reported cases of C. auris from otitis externa from 2009 to the end of 2016.…”
Section: Discussionmentioning
confidence: 94%
“…Candida auris is an emerging serious public health threat with high mortality and morbidity that can range from mild superficial infections to fungemia . Since the first case of C. auris in 2009, numerous cases and several outbreaks have been reported from all continents . The global increase in reports of C. auris , transmission in healthcare facilities, frequent relapse and treatment failures qualifies C. auris as one of the top‐ten most serious fungal pathogens .…”
Section: Introductionmentioning
confidence: 99%
“…127 Epidemiology and transmission C auris has been associated with multiple nosocomial outbreaks, especially in the intensive care setting. [139][140][141][142][143][144] An evaluation of C auris in New York City health care facilities demonstrated epidemiologic links between cases in multiple hospitals and long-term care facilities. 138 Importantly, colonization with C auris has been detected at multiple body sites including nares, groin, axilla, and rectum.…”
Section: Aurismentioning
confidence: 99%